“Estrategias comunicacionales y su relación con el posicionamiento del Patronato de Amparo Social de Latacunga’’ - Becerra Calderón, Karen Abigail (2024)
The objective of this investigation project was to determine existing relationship between communicational strategies and the positioning of Patronato Municipal de Latacunga, on communication department in relation to the use of communicational strategies for tree specific lines: social networking, media and the facilities of the institution, came into the deduction that the lack of budget and staff limits the effective implementation of their communicational strategies, which may come into a negative impact on the organization’s position. For project execution, a quantitative approach was implemented, with a descriptive level with a non-experimental design basis, on which a 7,145 population of the board users in area health. At its facilities was considered with a simple aleatory sampling on 366 users, whom the corresponding survey was applied to. The results that were obtained demonstrate the existence of a considerable positive correlation between the communicational strategies and the positioning of Patronato Municipal de Latacunga. Moreover, one of the contributions of this